2021
DOI: 10.1177/15266028211036480
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Revascularization of Tibial Arteries in Patients with Critical Limb Ischemia: Plantar-Arch Versus Transpedal Approach

Abstract: Purpose: To compare retrograde plantar-arch and transpedal-access approach for revascularization of below-the-knee (BTK) arteries in patients with critical limb ischemia (CLI) after a failed antegrade approach. Materials and Methods: Retrospectively we identified 811 patients who underwent BTK revascularization between 1/2014 and 1/2020. In 115/811 patients (14.2%), antegrade revascularization of at least 1 tibial artery had failed. In 67/115 (58.3%), patients retrograde access to the target vessel was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This fact becomes more apparent in cases with calcification of the occluded target vessels, increasing the likelihood of procedural failure. 8 The balloon-assisted retrograde puncture helps to overcome this scenario since it turns a plantar loop "indirect" approach of the opposite artery into a "direct" transpedal access. Stahlberg et al 8 have recently reported a significantly higher procedural success rate of the transpedal-access compared with the plantar arch approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact becomes more apparent in cases with calcification of the occluded target vessels, increasing the likelihood of procedural failure. 8 The balloon-assisted retrograde puncture helps to overcome this scenario since it turns a plantar loop "indirect" approach of the opposite artery into a "direct" transpedal access. Stahlberg et al 8 have recently reported a significantly higher procedural success rate of the transpedal-access compared with the plantar arch approach.…”
Section: Discussionmentioning
confidence: 99%
“…8 The balloon-assisted retrograde puncture helps to overcome this scenario since it turns a plantar loop "indirect" approach of the opposite artery into a "direct" transpedal access. Stahlberg et al 8 have recently reported a significantly higher procedural success rate of the transpedal-access compared with the plantar arch approach. One reason for this could be the shorter distance to the target lesion with increased pushability, since remarkably the technical success rate in both groupsdefined as access to the distal cap of the occlusion-did not differ significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation